STUDI LITERATUR PENGARUH PENGETAHUAN TENTANG POSYANDU TERHADAP KEPATUHAN IBU MELAKUKAN KUNJUNGAN POSYANDU - Sari, febi Ratna; Litaferina, Vindy; Wibisono, Ahmad Yunus Gunawan (Jurnal Surya, 2021)
Background: According to data from the Ministry of Health in 2017 the number of toddlers in Indonesia reached 23,848,283 toddlers, with the number of Integrated Healthcare Center in Indonesia totaling 294,428 Integrated Healthcare Center toddlers, of the total number of toddlers Integrated Healthcare Center of 57.43% namely active Integrated Healthcare Center and 42.57% namely Integrated Healthcare Center is not active. The data shows that there is still a gap between active Integrated Healthcare Center that is 100% and active Integrated Healthcare Center that have not reached 100%. Objective: To inform the research that has been done relating to the Literature Study on the Effect of Knowledge of Integrated Healthcare Center on Compliance with Mothers to Make Integrated Healthcare Center Visits. Research Methods: The method used in this research is to use journal article searches by using keywords according to topics. Results and Conclusions: The results of this study indicate that there is a relationship between the Literature Study on the Effect of Knowledge of Integrated Healthcare Center on Compliance Mothers to Visit Integrated Healthcare Center.